Protocol for a multicentre randomiSed controlled TRial of IntraVEnous immunoglobulin versus standard therapy for the treatment of transverse myelitis in adults and children (STRIVE). Issue 5 (25th May 2015) - Absoud, M; Gadian, J; Hellier, J; Brex, P A; Ciccarelli, O; Giovannoni, G; Kelly, J; McCrone, P; Murphy, C; Palace, J; Pickles, A; Pike, M; et al.
Abstract : Introduction: Transverse myelitis (TM) is an immune-mediated disorder of the spinal cord which causes motor and sensory disturbance and limited recovery in 50% of patients. Standard treatment is steroids, and patients with more severe disease appear to respond to plasma exchange (PLEX). Intravenous immunoglobulin (IVIG) has also been used as an adjunct to steroids, but evidence is lacking. We propose the first randomised control trial in adults and children, to determine the benefit of additional treatment with IVIG. Methods and analysis: 170 adults and children aged over 1 year with acute first episode TM or neuromyelitis optica (with myelitis) will be recruited over a 2.5-year period and followed up for 12 months. Participants randomised to the control arm will receive standard therapy of intravenous methylprednisolone (IVMP). The intervention arm will receive the above standard therapy, plus additional IVIG. Primary outcome will be a 2-point improvement on the American Spinal Injury Association (ASIA) Impairment scale at 6 months postrandomisation by blinded assessors. Additional secondary and tertiary outcome measures will be collected: ASIA motor and sensory scales, Kurtzke expanded disability status scale, International Spinal Cord Injury (SCI) Bladder/Bowel Data Set, Client Services Receipt Index, Pediatric Quality of Life Inventory, EQ-5D, SCI Pain and SCI Quality of Life Data Sets. Biological samples will be biobanked for future studies. After 6-months' follow-up of the first 52 recruited patients futility analysis will be carried out. Health economics analysis will be performed to calculate cost-effectiveness. After 6 months' recruitment futility analysis will be performed. Ethics and dissemination: Research Ethics Committee Approval was obtained: 14/SC/1329. Current protocol: v3.0 (15/01/2015). Study findings will be published in peer-reviewed journals. Trial registration numbers: This study is registered with EudraCT (REF: 2014-002335-34), Clinicaltrials.gov (REF: NCT02398994 ) and ISRCTN (REF: 12127581).